2014
DOI: 10.2310/7750.2013.13109
|View full text |Cite
|
Sign up to set email alerts
|

Off-Label Uses of Topical Vitamin D in Dermatology: A Systematic Review

Abstract: Topical vitamin D analogues have an important role in the off-label treatment of dermatologic disease, but higher quality studies are still required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 167 publications
(234 reference statements)
0
33
0
1
Order By: Relevance
“…Medical therapy of such event includes topical treatment with anti-inflammatory creams, lotions as well as topical corticosteroids (Carroll and Fleischer, 2004;Wat and Dytoc, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Medical therapy of such event includes topical treatment with anti-inflammatory creams, lotions as well as topical corticosteroids (Carroll and Fleischer, 2004;Wat and Dytoc, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review involving 165 articles showed a moderate to strong recommendation for the use of topical vitamin D analogues in combination with corticosteroids and phototherapy in vitiligo and as monotherapy for ichthyoses, morphea, pityriasis alba, prurigo nodularis, and polymorphous light eruption. It may be ineffective in the treatment of actinic keratosis, seborrheic keratosis, lichen planus, seborrheic dermatitis, alopecia areata, chemotherapy‐induced alopecia, and hypertrophic scars …”
Section: Off‐label Prescriptions In Dermatologymentioning
confidence: 99%
“…Additionally, anti‐inflammatory effects from the inhibition of cytotoxic T‐cells and NK cells and the downregulation of inflammatory cytokines were demonstrated (Bagot, Charue, Lescs, Pamphile, & Revuz, ; Rostkowska‐Nadolska et al, ). Calcipotriol, a synthetic topical vitamin D derivative, has been widely used in the treatment of psoriasis and has been reported to achieve beneficial effects in the treatment of other inflammatory diseases, such as morphea, vitiligo, and ichthyosis (Holm & Jemec, ; Wat & Dytoc, ). Generally, topical vitamin D analogues are well tolerated; nevertheless, common side effects after prolonged or excessive application are irritation and desquamation.…”
Section: Introductionmentioning
confidence: 99%
“…Calcipotriol, a synthetic topical vitamin D derivative, has been widely used in the treatment of psoriasis and has been reported to achieve beneficial effects in the treatment of other inflammatory diseases, such as morphea, vitiligo, and ichthyosis (Holm & Jemec, 2002;Wat & Dytoc, 2014). Generally, topical vitamin D analogues are well tolerated; nevertheless, common side effects after prolonged or excessive application are irritation and desquamation.…”
Section: Introductionmentioning
confidence: 99%